L’ombre de la merveille. Le merveilleux scientifique au second degré de Maurice Renard - Emilie Pézard (ReS Futurae)
The merveilleux scientifique can be treated in two different ways : the represensation of a true wonder within the fictional world ; or, on the contrary, a fake wonder that will prove to be an illusion. This article focuses on this second kind of stories that Maurice Renard wrote during all his career : this novelist that Claude Deméocq calls the « chantre du merveilleux-scientifique » (Deméocq, 1999) has also repeatedly written about the failure of the wonder. Based on a study of Les Mains d’Orlac and many short-stories, many of them unknown, this paper aims at showing that these apparently contradictory approaches are in fact complementary. Far from repeating the « explained surnatural » as Ann Radcliffe did use it in her novels, the failure of the wonder gives Maurice Renard a way to perform his project, « faire connaître à l’homme ce qu’il est » (1910). After a brief typology of the different status of the wonder in the fictional narratives of Maurice Renard, we analyse how the reader’s interest is transferred from the representation of the wonder to the way it is perceived by the character, and how this transfer allows Maurice Renard to integrate a theoretical reflection about the art of writing in his fictions.